Republic of Croatia : First Review Under the Stand-By Arrangement and Requests for Waiver of Nonobservance and Applicability of Performance Criteria. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
Croatia has made important strides in restoring robust economic growth and achieving price stability while continuing to strengthen its net international reserves position under the Stand-By Arrangement. Executive Directors welcomed this development, and stressed the need to improve fiscal consolidation, accelerate structural reforms, tighten monetary stance, and maintain the soundness of the banking system. They appreciated the budget, foreign exchange, labor laws, and emphasized the need to focus on public enterprise restructuring and privatization, and promote Croatia's European Union membership bid.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet